南極圏大気中の角運動量、熱、水蒸気輸送 - 中村, 昇; 佐藤, 薫; Noboru, Nakamura; Kaoru, Sato (2013)
The high-albedo, high-altitude continent surrounded by the Southern Ocean defines the unique role of the Antarctic region in the climate system. Lack of observation has long posed a significant challenge in our understanding of the maintenance and variability of the Antarctic climate, but thanks to advances in space-borne and ground-based observational networks as well as in the modern data assimilation techniques the Antarctic research has made strides in recent years. In this paper we will revisit the problem of angular momentum, heat, and moisture transport in the region and identify progress and remaining challenges. In particular, we will explore the relative importance of the Katabatic winds and the stratospheric forcing on the angular momentum budget, the effects of low-level coastal baroclinic disturbances on moisture transport and precipitation, and the role of ground-based observation such as PANSY in constraining the analyses. 第4回極域科学シンポジウム 特別セッション：[S] 南極研究の将来展望―第Ⅸ期6か年計画策定に向けて 11月14日（木） 国立極地研究所 ２階大会議室 conference object